Impacto do clareamento dental de consultório com peróxido de carbamida a 37% na mudança de percepção dos pacientes com o sorriso, alteração de cor e sensibilidade pós-operatória : ensaio clínico controlado randomizado simples-cego - Peixoto, Aline Carvalho (2018)
The aim of this study was to evaluate the impact of in-office tooth bleaching with 37% carbamide peroxide on patients' perceptions regarding the change in the satisfaction with their smile and on the bleaching procedures and their dental color change results and postoperative sensitivity when compared to 35% hydrogen peroxide. Forty patients were allocated to receive two sessions of in-office tooth bleaching using either 35% hydrogen peroxide (HP) or 37% carbamide peroxide (CP) (n=20). The perception of the smile itself was indicated through a visual analogue scale (VAS), and the procedures of tooth bleaching and its results were evaluated by means of a questionnaire applied 1 week after the first session and 30 days after the last one. Patients' sensitivity level was recorded during and up to 24 hours after bleaching procedure. Dental sensitivity was assessed using the verbal and EVA scales. It was calculated the absolute and relative risks to tooth sensitivity. The efficacy of bleaching procedures was evaluated with a spectrophotometer one week after each session and 30 days after the last one. Data from color evaluation (ΔL*, Δa*, Δb* and ΔE) were individually submitted to 2-way repeated measures ANOVA followed by Tukey’s post hoc test. Data from the level of sensitivity were analyzed by test Mann- Whitney. Absolute and relative risks were compared by the Fisher Exact test. It was observed a lower risk and level of tooth sensitivity for CP, while the difference between the bleaching agents disappeared after 24 hours. An increased bleaching effect was observed for HP, mainly due to an improved reduction of redness and yellowness. Participants perceived improved tooth bleaching for HP and reduced sensitivity for CP, but no differences regarding the comfort of the techniques were noted. An improved bleaching effect was observed for HP. CP resulted in reduced tooth sensitivity but also reduced the tooth bleaching efficacy. However, both bleaching agents resulted in high levels of patient satisfaction.